Triathlon Medical Coverage: A Guide for Medical Directors. Issue 4 (July 2017) - Asplund, Chad A.; Miller, Thomas K.; Creswell, Lawrence; Getzin, Andrew; Hunt, Andrew; Martinez, John; Diehl, Jason; Hiller, William D.; Berlin, Paul
Abstract : Interest and participation in triathlon has grown rapidly over the past 20 yr and with this growth, there has been an increase in the number of new events. To maximize the safety of participation, triathlons require medical directors to plan and oversee medical care associated with event participation. Provision of proper medical care requires knowledge of staffing requirements, common triathlon medical conditions, impact of course design, communication skill, and a familiarity of administrative requirements. These guidelines serve as a tool for triathlon medical and race directors to improve race safety for athletes.